Design of a Wide-Angle and Polarization-Free 1-Bit Programmable Metasurface - Liu, Lu; Huang, Yi Fei; Zhang, Hao Chi (Frontiers in Materials, 2022)
Programmable metasurfaces have the powerful capability of controlling electromagnetic (EM) waves by coding the digital state of each meta-atom. However, conventional programmable metasurface units are difficult to maintain stable controllability under wide-angle incidence conditions, which limits the application of 1-bit programmable metasurfaces in single-beam scanning. A 1-bit dual-polarized programmable metasurface that allows oblique incidence at large angles is presented in this article. Inspired by the principle of reciprocity in the antenna theory, a wide-angle patch antenna which operates in the receiving mode and is loaded by a PIN-diode–based load circuit is designed as the basic structure of the meta-atom. Numerical simulations show that the 1-bit coding state maintains good angular stability within ±70 degrees of the incident angle for both orthogonally polarized EM waves, and single-beam scanning can be achieved at large oblique incident angles for any polarization.